SUPPORT OF PERSPECTIVE BUSINESS PROCESSES IN THE REGIONS - A. Berkayeva (Вестник университета)
Following the results of 2015 in the Republic of the North Ossetia-Alania as a result of negative influence of external factors, and also in connection with a number of structural economic and social problems in the most important branches of economy has developed negative dynamics. A lifebuoy for rescue of economy of the republic is development of small and medium business and support of perspective business processes.